Three new species of Eugenia (Myrtaceae) from Brazilian Amazonia - Souza, Maria-Anália Duarte; Scudeller, Veridiana Vizoni; de Mendonça, Maria-Sílvia (Phytotaxa, 2015)
Three new species of Eugenia occurring in Brazilian Amazonian rainforest are described and illustrated: Eugenia kerianthera, Eugenia caducipetala and Eugenia marleneae. Eugenia kerianthera is related to Eugenia yasuniana, from which it is distinguished by its deltoid bracts and setaceous bracteoles, persistent and widely deltoid sepals, and oblong to obovate petals.  Eugenia caducipetala is similar to Eugenia exaltata but is differentiated by leaves with flat margins and midvein convex adaxially.  Eugenia marleneae is similar to Eugenia gomesiana and Eugenia trinervia, being distinguished from the first by its orbicular bracteoles and from the second by its fasciculate inflorescences. Phenological data, geographical distributions and further comparisons with morphologically similar species are provided.